About the kinetics and mechanism of the reactions of 4-(2-pyridylazo) resorcinol, with Zn2+, Cu2+ and Zn2+ +Cu2+ equimolar mixtures, in aqueous solutions - Rossi, Adriana Vitorino; Tubino, Matthieu (Eclética Química, 2003)
The kinetics and mechanism of the reactions between 4-(2-pyridylazo)-resorcinol and Zn 2 +, Cu 2+ and Zn 2+ +Cu 2+ equimolar mixtures were studied. The reactions were performed in aqueous solution (pH = 8.5, borate buffer) and monitored spectrophotometrically at 500 nm using stopped-flow technique. Spectral and kinetic data indicate that the Zn 2+ +Cu 2+ equimolar mixture behaves as an unique species and it can be attributed to the interactions of Zn 2+ and of Cu 2+ with water molecules in the aqueous solution. A mechanism is proposed and the rate constants are calculated.